Policing the frontier: an ethnography of two worlds in Niger - Göpfert, Mirco (Police/worlds studies in security, crime, and governance, 2020)
"This book explores what it means to be a gendarme investigating cases, writing reports, and settling disputes in a rural community in Niger and also addresses the irresolvable tension between bureaucratic forms and peoples' lives"--